VIDEO-BASED VEHICLE DETECTION ON A TWO-WAY ROAD - Zbigniew CZAPLA (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents a method of vehicle detection on a two-way road. Vehicle detection is carried out on the basis of the video stream from the camera placed over a road. The input image sequence is created by consecutive frames taken from the video stream. Images from the input image sequence are processed individually one by one. A detection field is defined for each lane of the road. Images from the input image sequence are converted into point image representation. The sums of the edge points within the detection fields are calculated. States of the detection fields are determined on the basis of calculated sums of the edge points. Vehicles are detected by analysis of states of the detection fields. Experimental results are provided.